2001
DOI: 10.1159/000051283
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Typical Pattern of Brain SPECT Imaging in Alzheimer’s Disease?

Abstract: The identification of new nosological forms such as Lewy body disease (LBD) requires a re-evaluation of the patterns observed in brain functional imaging in the various forms of dementia. We studied 60 demented patients, divided into three groups and fulfilling the clinical criteria for Alzheimer’s disease (AD), LBD and frontotemporal dementia (FTD), using Tc-HMPAO and a brain-dedicated SPECT system. After normalisation we applied a cut-off at two levels according to previously established criteria. We reaffir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…Patients in our study, who were classified according to this criterion, showed a grossly similar rCBF reduction in parietal, occipital, and cingulate regions between PDD and DLB, except for accentuated flow reduction in the frontal (premotor) cortex in DLB. Frontal flow reduction in DLB has also been shown in other studies [25,41]. The present results may be explained in part by findings that impairments in DLB are usually greatest in attentional and executive tasks, suggesting frontal involvement.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Patients in our study, who were classified according to this criterion, showed a grossly similar rCBF reduction in parietal, occipital, and cingulate regions between PDD and DLB, except for accentuated flow reduction in the frontal (premotor) cortex in DLB. Frontal flow reduction in DLB has also been shown in other studies [25,41]. The present results may be explained in part by findings that impairments in DLB are usually greatest in attentional and executive tasks, suggesting frontal involvement.…”
Section: Discussionsupporting
confidence: 88%
“…Statistical comparison was made between the patient groups and the control group in normalized patient and control images, in a pixel-by-pixel manner. Activity was normalized to mean activity in the cerebellum, considered the brain region least likely to be affected by PD [5,11,23,24] or dementia [25,26]. This type of intensity normalization was ultimately chosen over the standard method of proportional scaling to the mean global activity, which when initially tried gave clearly erroneous results in patients with dementia.…”
Section: Methodsmentioning
confidence: 99%
“…In FTLD, which accounts for approximately 20% of all pre-senile cases of dementia [159], the pathological changes are usually more circumscribed, affecting primarily frontal and temporal lobes [156]. Nevertheless, there is often selective anatomical degeneration within this group.…”
Section: Disorders: Ad -Alzheimer's Disease Agd -Argyrophilic Grain mentioning
confidence: 99%
“…When Steinling et al [20] studied AD, DLB and frontotemporal dementia (FTD) using technetium-99m hexamethylpropylene amine oxime (Tc-HMPAO) SPECT, they confirmed that patients with FTD have smaller bilateral frontal lobes and that patients with DLB have an extreme (yet diffuse) reduction in the size of the frontal lobes and the posterior association cortex. In AD patients, the reduction in brain size was found in the parieto-occipital cortex and was not related to the degree of a patient's cognitive decline.…”
Section: Functional Studies For Differentiating Dlb From Admentioning
confidence: 99%